AN REVIEW METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS (MRSA): CHARACTERIZATION, PREVALENCE AND ANTIBIOTIC REACTIONS ON HUMAN IN INDIA - Chaudhary, Megha; Kumar, Vinit; Singh, Sonika (Journal of Biomedical and Pharmaceutical Research, 2019)
Introduction: Community acquired MRSA (CA-MRSA) has been increasingly examined from India(4). A network of microbiology labs (Indian Organization for Surveillance of Antimicrobial Resistance - INSAR) at premier medical colleges and hospitals in India was assembled with support from the World Health Organization (figure). Prevalence of Methicillin Resistant Staphylococcus Aureus: A study displays an alarmingly high incidence of MRSA corruption in the BHU hospital. The prevalence rate is established to be 54.8%, which is much higher than most of the results where it ranged between 20% to 32.8%.(17),(18) The only report which has given somewhat similar result i.e. 51.6% is from LN Hospital, New Delhi.(19) Further, a study from Indore has shown a grow in MRSA prevalence from 12% in 1992 to 80.89% in 1999.(20) Modes of transmission and virulence factors: Due to its capability to colonize a wide range of strains (all mammals including rodents and lagomorphs), S. aureus can easily be transmitted from one species to another; from humans to animals and reverse. Staphylococcal infections are zoonotic in nature. Antibiotic Reaction on Human: The sensitivity patterns of divided to different antibiotic discs were read by measuring the diameter of area of inhibition in millimeter as per the chart provided by manufacturer and classified as Sensitive, Intermediate and Resistant based on CLSI guidelines.(8) Keywords: Antimicrobial, Bugs, Lagomorphs, MRSA, Rodent, Sensitivity, Staphylococcus.